Characterization of alternative oxidase (AOX) gene expression in response to methyl salicylate and methyl jasmonate pre-treatment and low temperature in tomatoes - Fung, Raymond W M (Journal of plant physiology, 2006)
Methyl salicylate (MeSA) vapor increased resistance against chilling injury (CI) in freshly harvested pink tomatoes. The expression patterns of alternative oxidase (AOX) before and during the chilling period demonstrated that pre-treatment of tomato fruit with MeSA vapor increased the transcript levels of AOX. We used 4 EST tomato clones of AOX from the public database that belong to two distinctly related families, 1 and 2 defined in plants. Three clones were designated as LeAOX1a, 1b and 1c and the fourth clone as LeAOX2. Using RT-PCR, 1a and 1b genes were found to be expressed in leaf, root and fruit tissues, but 1c was expressed preferentially in roots. RNA transcript from LeAOX1a of AOX subfamily 1 was present in much greater abundance than 1b or 1c. The presence of longer AOX transcripts detected by RNA gel blot analysis in cold-stored tomato fruit was confirmed to be the un-spliced pre-mRNA transcripts of LeAOX1a and LeAOX1b genes. Intron splicing of LeAOX1c gene was also affected by cold storage when it was detected in roots. This alternative splicing event in AOX pre-mRNAs molecules occurred, preferentially at low temperature, regardless of mRNA abundance. Transcript levels of several key genes involved in RNA processing (splicing factors: 9G8-SR and SF2-SR, fibrillarin and DEAD box RNA helicase) were also affected by changes in storage temperature. The aberrant splicing event in AOX pre-mRNA and its possible association with the change in expression of genes involved in RNA processing in tomato fruit having chilling disorder was discussed